2018
DOI: 10.1111/jwas.12523
|View full text |Cite
|
Sign up to set email alerts
|

Edible Corn‐zein‐based Coating Incorporated with Nisin or Lemongrass Essential Oil Inhibits Listeria monocytogenes on Cultured Hybrid Striped Bass, Morone chrysops × Morone saxatilis, Fillets During Refrigerated and Frozen Storage

Abstract: Listeria monocytogenes presents a serious threat to consumer safety because it is resistant to various food storage techniques, including reduced or modified atmosphere packaging, refrigerated storage, and increased salt concentration. Edible coatings incorporated with natural antimicrobials have been suggested to control pathogenic and spoilage bacteria on a variety of meat products. In this study, edible zein‐based coatings incorporated with nisin and lemongrass essential oil (LGEO; 8%) were evaluated for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…A lateral strip and two cross‐sectional pieces weighing approximately 25 g were removed and weighed in a Labplas 7.5″ × 12″ 4‐mil stomaching bag (Labplas, Quebec, Canada). Inoculation methods were as described in Hager, Rawles, Xiong, Newman, and Webster (), and briefly, a 1:10 dilution was made with peptone buffer, and the sample was pulverized in a stomacher for 1 min. For inoculated samples treated with nisin or LG, three dilutions each, ranging from 10 1 –10 3 and 10 2 –10 4 , respectively, were converted into a phosphate buffer (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…A lateral strip and two cross‐sectional pieces weighing approximately 25 g were removed and weighed in a Labplas 7.5″ × 12″ 4‐mil stomaching bag (Labplas, Quebec, Canada). Inoculation methods were as described in Hager, Rawles, Xiong, Newman, and Webster (), and briefly, a 1:10 dilution was made with peptone buffer, and the sample was pulverized in a stomacher for 1 min. For inoculated samples treated with nisin or LG, three dilutions each, ranging from 10 1 –10 3 and 10 2 –10 4 , respectively, were converted into a phosphate buffer (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…Costa, Maciel, Teixeira, Vicente, and Cerqueira (2018) mentioned that the incorporation of antimicrobials (nisin, natamycin, essential oils, lysozyme) in the starch‐based coating matrix resulted in a reduction of the spoilage, when considering post‐process contamination on the coating, since edible coatings have the capacity to maintain high concentrations of the active substance into the matrix preventing its migration and extended the shelf‐life. Likewise, Hager, Rawles, Xiong, Newman, and Webster (2019) reported that nisin contained in an edible coating (90,000 IU/15 ml film solution) based on corn‐zein has proven to be an effective bacteriocin against L. monocytogenes inoculated on the surface of a covered fish fillets (counts greater than 7 log in the non‐antimicrobial systems vs. 1 log counts in the nisin system on the fifth day of storage). Küçük, Çelik, Mazi, and Türe (2020) evaluated alginate and zein films as a carrier of natamycin in order to limit/prevent the mold growth on the surface of kashar cheeses.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Hager, Rawles, Xiong, Newman, and Webster (2019)) formulated a corn‐zein‐based edible coating incorporated with lemongrass oil (8%) and nisin (6 g). The authors coated fresh hybrid striped bass ( Morone chrysops × Morone saxatilis ) to inhibit the growth of Listeria monocytogenes under frozen and refrigerated storage.…”
Section: Application Of Antimicrobial Peptide‐loaded Coatings For Aqu...mentioning
confidence: 99%